GANGGUAN SEKSUAL TOKOH-TOKOH UTAMA DALAM NOVEL FIFTY SHADES OF GREY KARYA E. L JAMES - LAMBANAUNG, WIDYAWATI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
GANGGUAN SEKSUAL TOKOH-TOKOH UTAMA DALAM NOVEL FIFTY SHADES OF GREY KARYA F. SCOTT FITZGERALD Oleh: Widyawati Lambanaung   ABSTRACT As the requirement to accomplish the Bachelor Degree in English Literature at Faculty of Humanities in Sam Ratulangi University, this skripsi entitled “Sexual Disorder of the Major Characters in the novel Fifty Shades of Grey by E. L James is completed and submitted. The aims of this analysis are to analyze and classify the kind of ‘sexual disorder’ of the major characters in the novel Fifty Shades of Grey. The elaboration of major characters’ images, the characterization of the major characters, the identification and the classification the kinds of ‘sexual disorder’ is included and tied with the plot. Also, to describe the effects of “sexual disorder’ to the major characters themselves. Intrinsically, in characterization of the major characters, the paradigm by Stanton’ (1983) is chosen and extrinsically, in psychological analysis that is focused on sexual disorder of the major characters, the paradigm of abnormality characteristic and sexual disorder by Davison, Neale and Kring (2012) is used. The analysis is served by using descriptive method that is divided into intrinsic and extrinsic approaches. The intrinsic approach aims to analyze the major characters and the extrinsic approach is used to analyze the ‘sexual disorder’ of the major characters and its effects. The result of this analysis states that the major characters have the characteristic of abnormality in terms of sexual disorder. The major character Christian Grey has some kinds of sexual disorders: fetishism, voyeurism, froteurism, sadism sexual and masochism sexual. The major character Anastasia Steele has masochism sexual. The effects caused by the sexual disorder itself to the major characters, are: personal distress, determination, mental and physical inflictions, abnormality, destruction and separation of the relationship.